Syntheses, characterization and reactivity of iron(II), nickel(II), copper(II) and zinc(II) complexes of the ligand N,N,N ',N '-tetrakis(2-pyridylmethyl)-benzene-1,3-diamine (1,3-tpbd) and its phenol derivative 2,6-bis[bis(2-pyridylmethyl)amino]-p-cresol (2,6-tpcd) - Heinemann, Frank Wilhelm; et al. (European Journal of Inorganic Chemistry, 2007)
N,N,N',N'-Tetrakis(2-pyridylmethyl)benzene-1,3-diamine (1,3-tpbd), a bis(tridentate) ligand, its protonated derivative, [1,3-tpbdH(2)](2+), and a series of new dinuclear complexes [Fe-2(1,3-tpbd)(CH3CN)(6)](ClO4)(4)center dot(CH3CN)(2)center dot(H2O)(0.5) (1), [Fe-2(1,3-tpbd)(DMF)(6)](ClO4)(4) (2), [Ni-2(1,3-tpbd)(DMF)(6)](ClO4)(4) (3), [Zn-2(1,3-tpbd)(CH3CN)(2)(SO3CF3)(2)(H2O)](SO3CF3)(2) (4), [Zn-2(1,3-tpbd)Cl-4]center dot H2O (5), [CuZn(1,3-tpbd)Cl-4] (7) and the tetranuclear copper(II) complex [Cu-2(1,3-tpbd)(2)(H2O)(2)](ClO4)(4)center dot 2H(2)O (8) have been prepared and structurally characterized. Complex 8, a so called "dimetallocyclophane", interestingly only formed in the presence of zinc ions and not when copper(II) ions were mixed stoichiometrically (1:1 mixtures) under aerobic conditions. Theoretical calculations provide evidence for the formation of a side-on dinuclear peroxido copper complex during the oxidation of the (1, 3-tpbd) copper (1) complex. A possible reaction product, the dinuclear copper complex [Cu-2(2,6-tpcd)(H2O)(Cl)](ClO4)(2)center dot 2H(2)O (9) of a phenolate derivative of 1,3-tpbd was synthesized and structurally characterized independently from oxidation reactions from copper(II) perchlorate and the ligand 2,6-bis[bis(2-pyridylmethyl)amino]-p-cresol. ((c) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2007)
Keywords: iron; copper; zinc; ligand effects